الإمام السالمي و دوره الإصلاحي - الحوسني, حمود بن عبد الله بن هلال (كلية العلوم الشرعية, 2006)
Edition: الطبعة الأولى
Keywords: Réformisme – Oman

أثر الفكر الإصلاحي والتنويري لجمال الدين الأفغاني ومحمد عبده في عُمان نور الدين السالمي وأبو مسلم البهلاني (أنموذجاً) - الكاسبي, يوسف بن سعيد بن ناجم; الهادي, هاجر (مجلة العلوم الإسلامية, 2023)
Keywords: Réformisme – Oman

الشيخ نور الدين السالمي حياته وآثاره ومواقفه الإصلاحية والسياسية - شريفي, مصطفى بن محمد (جامعة الجزائر, 2001)
Keywords: Réformisme – Oman

دور الشيخ الحارثي في الإصلاح الإجتماعي - الحارثي, راشد بن علي (2017)
Keywords: Réformisme – Oman

Mediating Knowledge: The Circulation of Fatwas between Oman and the Maghreb at the turn of the 20th century - Ghazal, Amal N. (2019)
Keywords: Réformisme – Oman

أبو مسلم البهلانى وإسهاماته فى حركة الإصلاح - الوائلى, سعيد بن محمد بن شيخان (جامعة الزيتونة, 2002)
Keywords: Réformisme – Oman

الفكر الإصلاحي.. مفهومه ودور العُمانيّين فيه - الحجري, سلطان بن عبيد (التفاهم, 2016)
Keywords: Réformisme – Oman

Mascate a travers les cartes postales anciennes - Béguin-Billecocq, Xavier (Relations internationales et culture, 2007)
Keywords: Réformisme – Oman

Oman and Omani identity during the nahḍahs: A Comparison of Three Modern Historiographic Works - Coppola, Anna Rita (Oriente Moderno, 2014)
The present article analyzes the historiographic works of three Omani ʿulamāʾ during the twentieth century. It tries to contextualize them in the historical period in which they were written, showing the peculiarity of Omani literature in the context of the Arab world. This is due to various factors: first of all the development of its history constantly characterized by the Ibadhi religion. For example the nahḍah and the reformism have taken on different meanings in Oman, especially in the modernizing era of Sultan Qābūs’s rule. Omani historiography is part and the product of this peculiarity. It narrates the changes and events in Oman and shows how the historiographer is affected by history, culture and religion.
Keywords: Réformisme – Oman

A Historic Perspective on the Nahḍa - Wilkinson, John Craven (Oman, Ibadism and modernity, 2018)
Keywords: Réformisme – Oman

Nūr al-Dīn al-Sālimī (1286-1332/1869-1914) and Islamic Reform in the Modern Identity Context - Zdanowski, Jerzy (Local and global Ibadi identities, 2019)
Keywords: Réformisme – Oman